2018
DOI: 10.1111/jop.12722
|View full text |Cite
|
Sign up to set email alerts
|

The expression of programed death ligand‐1 could be related with unfavorable prognosis in salivary duct carcinoma

Abstract: High PD-L1 expression in SDC was strongly associated with unfavorable prognosis, indicating that PD-1/PD-L1 inhibitors could be effective in SDC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Five of our cases exhibited low level (1%‐8%) PD‐L1 expression in tumor cells. A recent study by Sato et al, which utilized the PD‐L1 clone E1L3N (Cell Signaling Technology), revealed higher rates of PD‐L1 expression in SDC tumor cells, with 4 of 18 cases showing high expression (defined as greater than 10%) and 5 of 18 cases showing low expression (1%‐9%); moreover high PD‐L1 expression strongly correlated with shorter overall survival. In our study, two different anti‐PD‐L1 assays (laboratory developed SP142 assay and 28‐8 complementary diagnostic assay used for head and neck squamous cell carcinoma) were used in 2 different groups of cases, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Five of our cases exhibited low level (1%‐8%) PD‐L1 expression in tumor cells. A recent study by Sato et al, which utilized the PD‐L1 clone E1L3N (Cell Signaling Technology), revealed higher rates of PD‐L1 expression in SDC tumor cells, with 4 of 18 cases showing high expression (defined as greater than 10%) and 5 of 18 cases showing low expression (1%‐9%); moreover high PD‐L1 expression strongly correlated with shorter overall survival. In our study, two different anti‐PD‐L1 assays (laboratory developed SP142 assay and 28‐8 complementary diagnostic assay used for head and neck squamous cell carcinoma) were used in 2 different groups of cases, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…There are a few differences between our study and the two previously mentioned studies [13,19]. Firstly, we did not stratify the PD-L1 expression into high and low; and simply considered immunoreactivity of ≥ 1% as positive.…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study of recurrent or metastatic salivary gland carcinomas with PD-L1 expression in ≥1% of tumor or stromal cells, pembrolizumab demonstrated some anti-tumor activity, with a confirmed objective response rate of 12% (95% confidence interval, 2%−30%) after a median followup of 20 months [18]. With respect to SDC only, a recent study of 18 patients found that high PD-L1 expression (defined in the study by positivity in > 10% of tumor cells) was strongly associated with unfavorable prognosis and shorter overall survival (log-rank test: p = .0045) [19]. In a study of 219 salivary gland tumors, which included 31 cases of SDC, PD-L1 expression was associated with reduced 5 year disease free survival as well as overall survival (p = < 0.001) [13].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Most SDC cases are microsatellite‐stable and have a low TMB 59,63,70,73,82 . There are no consistent data on PD‐L1 expression 59‐64 . A study of immune checkpoint inhibitor (pembrolizumab) treatment for advanced salivary gland carcinoma reported a 12% response rate, and another study of pembrolizumab included 1 SDC case in the cohort 109,110 .…”
Section: Treatmentmentioning
confidence: 99%